The role of culture in building regional innovation systems and its impact on business tourism – The case of the Nuremberg Metropolitan Region - BIALK-WOLF, Anna; PECHLANER, Harald; NORDHORN, Christian (Economics and Business Review, 2013)
In recent years increased attention has been paid to the role of culture and creativity as significant factors infl uencing economic development. Another crucial phenomenon shaping the economy is the great importance of regionalism. Culture, creativity and regionalism seem to facilitate coping with the troubles of our times in a better way. This paper aims to contribute to a better understanding of the ways culture and creativity influence the building of a regional innovation system. A review of crucial literature considering the regional innovation system and the role of culture and creativity in the economic development is provided. The conclusion from qualitative research suggests that the signifi cance of creativity in the Nuremberg Metropolitan Region is widely acknowledged and is an attempt to exploit this finding.